2012
DOI: 10.1136/bmjopen-2012-001574
|View full text |Cite
|
Sign up to set email alerts
|

The organising vision for telehealth and telecare: discourse analysis

Abstract: ObjectiveTo (1) map how different stakeholders understand telehealth and telecare technologies and (2) explore the implications for development and implementation of telehealth and telecare services.DesignDiscourse analysis.Sample68 publications representing diverse perspectives (academic, policy, service, commercial and lay) on telehealth and telecare plus field notes from 10 knowledge-sharing events.MethodFollowing a familiarisation phase (browsing and informal interviews), we studied a systematic sample of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
190
1
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 174 publications
(199 citation statements)
references
References 43 publications
2
190
1
6
Order By: Relevance
“…The approach has been applied to healthcare studies since the 1990s, though not yet with great frequency. [7][8][9][10][11] bIAses of trAdItIonAl reseArch ApproAches versus Internet forum-bAsed dIscourse AnAlysIs The assessment of patients' behaviour for research purposes is fraught with difficulties (Box 1). 12 One of the problems of measuring behaviours is that the act of measurement can itself influence behaviour.…”
Section: Discourse Analysismentioning
confidence: 99%
“…The approach has been applied to healthcare studies since the 1990s, though not yet with great frequency. [7][8][9][10][11] bIAses of trAdItIonAl reseArch ApproAches versus Internet forum-bAsed dIscourse AnAlysIs The assessment of patients' behaviour for research purposes is fraught with difficulties (Box 1). 12 One of the problems of measuring behaviours is that the act of measurement can itself influence behaviour.…”
Section: Discourse Analysismentioning
confidence: 99%
“…[3][4][5][6][7][8][9] The £31 million Department of Health Whole Systems Demonstrator trial suggested that tele-health was associated with a statistically significant reduction in morbidity, mortality and use of conventional health services, if used correctly with appropriate staffing and organisational infrastructure, although this study has been criticised for 'pro-innovation bias' and failing to engage effectively with the social and psychological aspects of the use of technology in chronic illness care. 10 Conventional methods for improving self-management have often been personnel-intensive, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Technology Enabled Care Services that encompass telehealth, telecare, telemedicine, telecoaching and self-care apps with remote video consultation are starting to be used in rural countries such as Australia. 5 This technology is also developing in the UK, although current evidence for its effectiveness and cost effectiveness is mixed, and strong barriers to adoption remain (Greenhalgh et al 2012;Henderson et al 2013). Consumer preferences are likely to play an important role in their success.…”
Section: Next-generation Ictmentioning
confidence: 99%